Clinical value of neutrophil-to-lymphocyte ratio and prognostic nutritional index on prediction of occurrence and development of diabetic foot-induced sepsis - Sun, Bing; Chen, Yimin; Man, Yulin; Fu, Yu; Lin, Jianchang; Chen, Zhaohong (Frontiers in Public Health, 2023)
Background Diabetic foot-induced sepsis is a serious complication associated with increased disability and mortality in hospitalized patients. Early prediction of admission and detection effectively improve treatment options and prevent further deterioration. This study aims to evaluate the clinical value of the neutrophil-to-lymphocyte ratio (NLR) and prognostic nutritional index (PNI) to predict the risk of sepsis in patients with diabetic foot ulcers (DFU). Methods Retrospective analysis was performed on 216 patients who were admitted to the Fujian Medical University Union Hospital between January 2015 and December 2022. Patients with DFU were divided into the non-sepsis (n = 166) and the DFU-induced sepsis (n = 50) groups. The independent factors of DFU-induced sepsis were determined by univariate and multivariate logistic regression analyses. A receiver operating characteristic (ROC) curve was performed to compare the area under the curves (AUC) of PNI and NLR. Results Multivariate logistic regression analysis revealed that the PNI, NLR, international normalized ratio (INR), thrombin time (PT), and C-reactive protein (CRP) were independent prognostic factors for DFU-induced sepsis. After adjusting for potential confounders, the adjusted odds ratios of NLR for DFU-induced sepsis were 1.121 (1.072–1.172), 1.132 (1.077–1.189), and 1.080 (1.022–1.142), while those of PNI were 0.912 (0.873–0.953), 0.902 (0.856–0.950), and 1.004 (1.001–1.006). Moreover, the AUC of NLR was significantly greater than that of CRP (0.790, 95% CI: 0.689–0.891, p < 0.001 vs. 0.780, 95% CI: 0.686–0.873, p < 0.001). Conclusion NLR and PNI have been regarded as readily and independently predictive markers in patients with DFU-induced sepsis. NLR is critical for the early detection and effective treatment of DFU-induced sepsis and is superior to CRP.